The Potential Role of fNIRS in Evaluating Levels of Consciousness - Abdalmalak, Androu; Milej, Daniel; Norton, Loretta; Debicki, Derek B.; Owen, Adrian M.; Lawrence, Keith St. (Frontiers in Human Neuroscience, 2021)
Over the last few decades, neuroimaging techniques have transformed our understanding of the brain and the effect of neurological conditions on brain function. More recently, light-based modalities such as functional near-infrared spectroscopy have gained popularity as tools to study brain function at the bedside. A recent application is to assess residual awareness in patients with disorders of consciousness, as some patients retain awareness albeit lacking all behavioural response to commands. Functional near-infrared spectroscopy can play a vital role in identifying these patients by assessing command-driven brain activity. The goal of this review is to summarise the studies reported on this topic, to discuss the technical and ethical challenges of working with patients with disorders of consciousness, and to outline promising future directions in this field.